(untitled) (Revista da Tulha, 2016)
In the middle of the recent cultural movement of the “viola caipira”, the orchestras of Violeiros stand out. Since the pioneering creation of the Osasco’s “Violeiros Orchestra” in 1967, dozens of similar musical ensembles have sprung up and spread throughout centralsouthern Brazil. It is a musical formation composed by several players of “viola caipira”, with repertoire constituted mainly by the well-known country songbook. Participating in the orchestras instrumentalists of different ages, scholarity, gender, musical formation, origins and social contexts, gathered around the culture and values of the country, with the objective of maintaining tradition, learning the instrument and transmitting viola’s techniques. The Orchestras have been guards of the repertoire and the tradition of the viola, contributing to the survival of the old music “sertaneja” in the margins of the music industry. On the other hand, they carry with them innovations in the musical language of the country repertoire, through new orchestrated instrumental arrangements. It is concluded that Orchestras engender a very particular form of sociability, where the tradition and the modern, the rural and the urban are found. They are, at the same time, spaces for the renewal of the instrument and preservation of the memory and values of rural culture. They represent, in short, a synthesis of the recent transformations of the “viola caipira”. In view of the large number of “violeiros” who participate in the Orchestras today, an in-depth investigation and mapping of this phenomenon is essential. This work presents an overview of these musical groups in Brazil and reflections that serve as a basis for a research that aims at understanding the social and musicological aspects of Orchestras.